PERCEPTION OF OWN WELL-BEING IN THE IN-CULTURAL ENVIRONMENT AS A PREDICTOR OF TRAINING MOTIVATION OF FOREIGN STUDENTS - Vladimir Solomonov (Вестник Северо-Кавказского федерального университета)
The article examines the results ofan empirical study of the motivation ofstudents' academic activity from foreign countries, the impact of foreign students' perception of their own well-being in a different socio-cultural environment on the motivation of their educational activities. It is established that the perception of one's own well-being in an inocultural environment is interconnected with the characteristics of educational motivation and has a pronounced cross-cultural specifics that should be taken into account when dealing with foreign students at a university.